Influence of the mode of heating on cerebral blood flow, non‐invasive intracranial pressure and thermal tolerance in humans. (2nd March 2021) - Gibbons, Travis D.; Ainslie, Philip N.; Thomas, Kate N.; Wilson, Luke C.; Akerman, Ashley P.; Donnelly, Joseph; Campbell, Holly A.; Cotter, Jim D.
Abstract : Key points: The human brain is particularly vulnerable to heat stress; this manifests as impaired cognition, orthostatic tolerance, work capacity and eventually, brain death. The brain's limitation in the heat is often ascribed to inadequate cerebral blood flow (CBF), but elevated intracranial pressure is commonly observed in mammalian models of heat stroke and can on its own cause functional impairment. The CBF response to incremental heat strain was dependent on the mode of heating, decreasing by 30% when exposed passively to hot, humid air (sauna), while remaining unchanged or increasing with passive hot‐water immersion (spa) and exercising in a hot environment. Non‐invasive intracranial pressure estimates (nICP) were increased universally by 18% at volitional thermal tolerance across all modes of heat stress, and therefore may play a contributing role in eliciting thermal tolerance. The sauna, more so than the spa or exercise, poses a greater challenge to the brain under mild to severe heating due to lower blood flow but similarly increased nICP. Abstract: The human brain is particularly vulnerable to heat stress; this manifests as impaired cognitive function, orthostatic tolerance, work capacity, and eventually, brain death. This vulnerability is often ascribed to inadequate cerebral blood flow (CBF); however, elevated intracranial pressure (ICP) is also observed in mammalian models of heat stroke. We investigated the changes in CBF with incremental heat strain under three fundamentally different modes of heating, and assessed whether heating per se increased ICP. Fourteen fit participants (seven female) were heated to thermal tolerance or 40°C core temperature ( T c ; oesophageal) via passive hot‐water immersion (spa), passive hot, humid air exposure (sauna), cycling exercise, and cycling exercise with CO2 inhalation to prevent heat‐induced hypocapnia. CBF was measured with duplex ultrasound at each 0.5°C increment in T c and ICP was estimated non‐invasively (nICP) from optic nerve sheath diameter at thermal tolerance. At thermal tolerance, CBF was decreased by 30% in the sauna ( P < 0.001), but was unchanged in the spa or with exercise ( P ≥ 0.140). CBF increased by 17% when end‐tidal P C O 2 was clamped at eupnoeic pressure ( P < 0.001). On the contrary, nICP increased universally by 18% with all modes of heating ( P < 0.001). The maximum T c was achieved with passive heating, and preventing hypocapnia during exercise did not improve exercise or thermal tolerance ( P ≥ 0.146). Therefore, the regulation of CBF is dramatically different depending on the mode and dose of heating, whereas nICP responses are not. The sauna, more so than the spa or exercise, poses a greater challenge to the brain under equivalent heat strain. Key points: The human brain is particularly vulnerable to heat stress; this manifests as impaired cognition, orthostatic tolerance, work capacity and eventually, brain death. The brain's limitation in the heat is often ascribed to inadequate cerebral blood flow (CBF), but elevated intracranial pressure is commonly observed in mammalian models of heat stroke and can on its own cause functional impairment. The CBF response to incremental heat strain was dependent on the mode of heating, decreasing by 30% when exposed passively to hot, humid air (sauna), while remaining unchanged or increasing with passive hot‐water immersion (spa) and exercising in a hot environment. Non‐invasive intracranial pressure estimates (nICP) were increased universally by 18% at volitional thermal tolerance across all modes of heat stress, and therefore may play a contributing role in eliciting thermal tolerance. The sauna, more so than the spa or exercise, poses a greater challenge to the brain under mild to severe heating due to lower blood flow but similarly increased nICP.